The Effect of Murottal Al-Qur'an Therapy on Improving Study Concentration in College Students - Nasywa Syahira Oktaviani; Vetty Erista; Dwi Putri Agustin; Karima Alya; Nur Shofiyyah Azizah Syafril (Journal of Islamic Psychology and Behavioral Sciences, 2024)
This article presents a study regarding the effect of Al-Qur'an therapy on increasing concentration in psychology students. This research used a quantitative quasi-experimental design with pre-test post-test to measure the impact of Al-Qur'an therapy on concentration. The research results showed a significant increase in concentration in students after undergoing Al-Qur'an therapy. Statistical analysis revealed striking differences between the control and experimental groups. In addition, this research also highlights the impact of anxiety as a factor that influences individual concentration. This research aims to provide empirical evidence regarding the effectiveness of Al-Qur'an therapy in increasing concentration in students.